Display life and internal cooked color of ground beef from vitamin e-supplemented cattle - Lavelle, C.L.; Hunt, Melvin C.; Kropf, Donald H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Retail display life of ground beef and internal color of patties cooked to four endpoint temperatures (131, 149, 160, and 17 1EF) were determined for ground beef (9% fat) from vitamin E-supplemented (500 and 2000 IU per day) steers. Visual scores indicated that the display time required for the 500 and 2000 vitamin E samples to reach an objectionable reddish-brown/brown color was increased by 12 and 32 hours, respectively, as compared with the 0 vitamin E samples. Patties did not differ in internal cooked color regardless of vitamin E level. Vitamin E was effective in increasing retail display color stability and did not affect cooked color.
Keywords: Beef; Visual display; Cooked color; Vitamin E; Ground beef; Color